The Effect of the Weight Reduction on the Salivary Cortisol Levels of Judo Players - Toda, Masahiro; Morimoto, Kanehisa; Fukuda, Sanae; Umeda, Takashi; Nakaji, Shigeyuki; Sugawara, Kazuo (Environmental Health and Preventive Medicine, 2001)
The purpose of this study was to investigate the effect of weight reduction prior to a competition on the salivary cortisol level for first-rate judo players. Subjects were divided into three groups by the weight reduction rate. On the day before the competition, the cortisol levels of the low- and high-weight reduction group showed a tendency to decrease and were significantly lower than that of the non-weight reduction group (p<0.05). However, with regard to the change in the stress indices, there was a difference between the high- and low-weight reduction groups. In the high-weight reduction group alone, there was a significant increase in the stress indices on the day before the competition (p<0.05). These findings suggest that the HPA axis is affected during the relatively early stage of weight reduction and mental stress is increased at the higher weight reduction rate.